Comparison of echocardiographic parameters between pre-clinical and clinical advanced diastolic dysfunction patients. (1st December 2016) - Carasso, Shemy; Williams, Lynne K.; Hazanov, Yevgeni; Halhla, Yussra; Ghanim, Diab; Amir, Offer
Abstract: Background: The diagnosis of heart failure (HF) with preserved ejection fraction requires evidence of grade 2 or 3 (advanced) diastolic dysfunction (ADD), but many patients with ADD do not have clinical HF manifestations, hence termed pre-clinical diastolic dysfunction (PDD). The prevalence and characteristics of PDD in comparison to overt HF disease (clinical-ADD) are still debated. Methods: We retrospectively analyzed 373 patients with LVEF ≥ 45% and ADD in our echo-lab database. Exclusion criteria were acute coronary syndromes, ≥ moderate valvular disease, cardiomyopathies or pericardial disease. Patients were divided into 2 groups according to the presence/absence of HF symptoms, namely PDD ( n = 249) and clinical-ADD ( n = 124). Demographic, clinical and echocardiographic parameters were compared between the groups. Results: Age, gender and comorbidities were similar between groups, with only a higher body mass index and renal failure significantly more prevalent in the clinical-ADD patients. Neither LV mass nor the ADD severity was related to the presence of symptoms; lateral mitral E/E′ and pulmonary artery systolic pressure were significantly higher in clinical-ADD patients (14 ± 5 vs. 12 ± 4, p < 0.05 and 40 ± 13 vs. 36 ± 11 mm Hg, p < 0.05, respectively) and were the only parameters to correlate with the presence of symptoms of clinical-ADD in multivariable logistic regression (odds ratio = 1.07 (CI 1.02–1.1, p = 0.008) and 1.03 (CI 1.01–1.05, p = 0.01), respectively). Conclusions: In patients referred for an echocardiogram at a community cardiology center, PDD was twice as common as clinical-ADD. Hemodynamic parameters reflecting elevated filling and pulmonary pressures, rather than traditional comorbidities and/or classical structural abnormalities, were the only parameters related to the presence of HF symptoms.